Organizational Issues, Structure, and Processes of Care in 257 ICUs in Latin America: A Study From the Latin America Intensive Care Network. Issue 8 (August 2017) - Estenssoro, Elisa; Alegría, Leyla; Murias, Gastón; Friedman, Gilberto; Castro, Ricardo; Nin Vaeza, Nicolas; Loudet, Cecilia; Bruhn, Alejandro; Jibaja, Manuel; Ospina-Tascon, Gustavo; Ríos, Fernando; Machado, Flavia R.; et al.
Abstract : Objective: Latin America bears an important burden of critical care disease, yet the information about it is scarce. Our objective was to describe structure, organization, processes of care, and research activities in Latin-American ICUs. Design: Web-based survey submitted to ICU directors. Settings: ICUs located in nine Latin-American countries. Subjects: Individual ICUs. Interventions: None. Measurements and Main Results: Two hundred fifty-seven of 498 (52%) of submitted surveys responded: 51% from Brazil, 17% Chile, 13% Argentina, 6% Ecuador, 5% Uruguay, 3% Colombia, and 5% between Mexico, Peru, and Paraguay. Seventy-nine percent of participating hospitals had less than 500 beds; most were public (59%) and academic (66%). ICUs were mainly medical-surgical (75%); number of beds was evenly distributed in the entire cohort; 77% had 24/7 intensivists; 46% had a physician-to-patient ratio between 1:4 and 7; and 69% had a nurse-to-patient ratio of 1 ≥ 2.1. The 24/7 presence of other specialists was deficient. Protocols in use averaged 9 ± 3. Brazil (vs the rest) had larger hospitals and ICUs and more quality, surveillance, and prevention committees, but fewer 24/7 intensivists and poorer nurse-to-patient ratio. Although standard monitoring, laboratory, and imaging practices were almost universal, more complex measurements and treatments and portable equipment were scarce after standard working hours, and in public hospitals. Mortality was 17.8%, without differences between countries. Conclusions: This multinational study shows major concerns in the delivery of critical care across Latin America, particularly in human resources. Technology was suboptimal, especially in public hospitals. A 24/7 availability of supporting specialists and of key procedures was inadequate. Mortality was high in comparison to high-income countries. Abstract : Supplemental Digital Content is available in the text.